PENGARUH GAYA KEPEMIMPINAN, BUDAYA ORGANISASI DAN KECERDASAN EMOSIONAL TERHADAP LEARNING ORGANIZATION PADA BADAN PENGEMBANGAN SUMBER DAYA MANUSIA HUKUM DAN HAM KEMENTERIAN HUKUM DAN HAM RI - Regiana, Lita (Operations Excellence: Journal of Applied Industrial Engineering, 2016)
Abstract. Substitution of leader that causes changes in leadership style, the presence of factors inhibiting the work culture of discipline and ability to adapt and percentage of employees who participate in training are problems that can hinder learning organization. This study aimed to examine the effect of leadership styles, organizational culture and emotional intelligence toward learning organization in the Human Resources Development Agency of Law and Human Rights, Ministry of Law and Human Rights. This study used quantitative methods. The population of this study is all the employees of the Agency as many as 175 people. The sampling technique using probability sampling, with proportional random sampling, found a sample of 122 people, obtained by the formula Slovin. Data were analyzed using multiple regression analysis. The results showed that the leadership style, organizational culture and emotional intelligence partially and simultaneously have significant effect on learning organization. Transformational leadership style, learning culture and social skills have a more significant effect than the other dimensions to the dimensions of a learning organization. Transformational leaders, the formation of a culture of learning and the improvement of adaptability skills can promote the establishment of a learning organization. Keywords: leadership style, organizational culture, emotional intelligence learning organization.